Structural Insights into the Interactions between Platelet Receptors and Fibrillar Collagen - Herr, Andrew B. (American Society for Biochemistry and Molecular Biology, 2009)
Collagen peptides have been used to identify binding sites for several important collagen receptors, including integrin α(2)β(1), glycoprotein VI, and von Willebrand factor. In parallel, the structures of these collagen receptors have been reported, and their interactions with collagen peptides have been studied. Recently, the three-dimensional structure of the intact type I collagen fiber from rat tail tendon has been resolved by fiber diffraction. It is now possible to map the binding sites of platelet collagen receptors onto the intact collagen fiber in three dimensions. This minireview will discuss these recent findings and their implications for platelet activation by collagen.